Lineage tracing of acute myeloid leukemia reveals the impact of hypomethylating agents on chemoresistance selection - Francisco Caiado (Nature Portfolio, 2019)
The development of post-chemotherapy resistance is a significant issue in the management of AML. Here, Caiado et al. suggest that the issue might be circumvented via upfront combination with hypomethylating agents that shape the clonal dynamics and transcriptional landscape of relapsing AML